Creative Management And Development - Henry, Jane (Sage Publication, 2006)
Creative Management and Development has been updated with newly commissioned and leading edge chapters on intuitive cognition, complexity, emotion, team innovation, development, and well-being. The textbook retains seminal papers on creativity, perception, style, culture, and sustainable development.